Industrial Society in Discussion (Czech Journal of International Relations, 1967)
Today, few people doubt the necessity of a qualified and substantive dialogue between Marxists and representatives of non-Marxist schools of thought. There is no dispute that the isolation, characteristic of the previous period, the lack of possibility of direct confrontation led to stagnation of thought and argumentation. At the same time, however, the fact is sometimes overlooked that the dialogue that is being called for is already taking place, that we have a number of concrete results, which would be worth thinking about and perhaps even drawing some conclusions from.This is evidenced, for example, by the publication published by the West German Constitution for the Education of Citizens in the Rhineland-Palatinate under the common name Industrial Society in the East and the West. On the current topic - industrial society and its development tendencies - I have my say: Nestor of West German sociology Hans Freyer, political scientist Lothar Bossle of the University of Mohe and PhDr. Jindrich Filipec (Institute of Philosophy CSAV). As the editors note in the introduction, this is the first discussion of a similar type, already with a representative of a socialist state.